2003
DOI: 10.1302/0301-620x.85b6.14166
|View full text |Cite
|
Sign up to set email alerts
|

Levels of metal ions after small- and large-diameter metal-on-metal hip arthroplasty

Abstract: etal-on-metal (MOM) bearings for hip arthroplasty are increasing in popularity. Concern remains, however, regarding the potential toxicological effects of the metal ions which these bearings release.The serum levels of cobalt and chromium in 22 patients who had undergone MOM resurfacing arthroplasty were compared with a matched group of 22 patients who had undergone 28 mm MOM total hip arthroplasty (THA).At a median of 16 months (7 to 56) after resurfacing arthroplasty, we found the median serum levels of coba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
133
5
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(144 citation statements)
references
References 26 publications
5
133
5
1
Order By: Relevance
“…Although there are no published reports which directly compare ion levels in patients with MOM-BHR or MOM-THA, our data are in the range previously reported. Some authors have evaluated ion levels, but the studies either had short-term followup or they were not comparative studies of MOM-BHR versus MOM-THA (Table 4) [3,5,11,17,27,29,34,38,39]. In addition, we found time of followup and age had no influence on serum ion levels, whereas gender in association with implant type influenced Cr levels, with females who had MOM-BHR showing an increase in Cr levels compared with males who had MOM-BHR.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Although there are no published reports which directly compare ion levels in patients with MOM-BHR or MOM-THA, our data are in the range previously reported. Some authors have evaluated ion levels, but the studies either had short-term followup or they were not comparative studies of MOM-BHR versus MOM-THA (Table 4) [3,5,11,17,27,29,34,38,39]. In addition, we found time of followup and age had no influence on serum ion levels, whereas gender in association with implant type influenced Cr levels, with females who had MOM-BHR showing an increase in Cr levels compared with males who had MOM-BHR.…”
Section: Discussionmentioning
confidence: 74%
“…All metal implants corrode at a rate which is determined partly by their surface area [4]. For this reason, the introduction of large-diameter MOM bearings, as used in MOM-BHR, has prompted even more concern [5]. However, the large diameter and low radial clearance of MOM bearings are key factors in reducing dry contact and hydrodynamic pressures and important in improving lubrication performance [25].…”
Section: Introductionmentioning
confidence: 99%
“…The trend in our results also agrees with that reported by Daniel et al [6] for the same followup in a study of BHR with bearing diameters of 50 mm and 54 mm versus 28-mm Metasul 1 MOM THA, in which whole blood samples were analyzed. In contrast, Clarke et al [5], at a median of 16 months, reported higher median Co and Cr serum levels in patients who had hip resurfacing arthroplasty compared with patients who had MOM THAs. Unlike our study, Clarke et al [5] used two different prosthetic designs.…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, Clarke et al [5], at a median of 16 months, reported higher median Co and Cr serum levels in patients who had hip resurfacing arthroplasty compared with patients who had MOM THAs. Unlike our study, Clarke et al [5] used two different prosthetic designs. One was the double heat-treated Cormet 2000 TM (Corin Group PLC, Cirencester, UK) (carbide volume fraction, 2.3%) and the other was the as-cast BHR (carbide volume fraction, 5%).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation